L-carnitine supplementation in patients with HIV/AIDS and fatigue: a double-blind, placebo-controlled pilot study - Cruciani RA (Dove Medical Press, 2015)
Ricardo A Cruciani,1 Manuel Revuelta,2 Ella Dvorkin,3 Peter Homel,4 Pauline Lesage,5 Nora Esteban-Cruciani6 1Center for Comprehensive Pain Management and Palliative Care, Capital Institute for Neurosciences, Capital Health Medical Center, Pennington, NJ, 2Lee Memorial Hospital, Fort Myers, FL, 3Institutional Review Board, New York University, New York, NY, 4Department of Pain Medicine and Palliative Care, Beth Israel Medical Center, New York, NY, 5Maimonides Medical Center, Brooklyn, NY, 6Children's Hospital at Montefiore, Albert Einstein College of Medicine, Bronx, NY, USA Background: The purpose of this study was to determine the effect of L-carnitine supplementation on fatigue in patients with terminal human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS). Methods: In this randomized, double-blind, placebo-controlled, parallel-group study, patients who had end-stage HIV/AIDS with carnitine deficiency and fatigue received 3 g of oral L-carnitine or placebo for 2 weeks, followed by a 2-week, open-label phase with the same amount of L-carnitine for all patients. The primary outcome was the degree of fatigue according to the Brief Fatigue Inventory. Secondary outcomes included serum carnitine and lactate levels, physical, emotional, social, and functional well-being, performance status, mood, and CD4 count. Results: Eighteen patients in the treatment arm and 17 in the placebo arm completed the trial. At the end of the double-blind phase, total and free carnitine levels in the treatment arm rose from 28±9 to 48±17 nM/L (P<0.001) and from 24±8 to 40±13 nM/L (P<0.001) respectively, with no changes in the placebo arm. The primary outcome, ie, fatigue measured at the end of the blinded phase, did not improve. Secondary outcomes of function, quality of life, and mood did not show improvement either. The secondary outcome of serum lactate decreased from baseline in the treatment group (1.45±0.76 to 1.28±0.52 mmol/L) and increased in the placebo group (1.38±0.62 to 1.84±0.74 mmol/L; P<0.005). Conclusion: Our study suggests that 3 g of oral L-carnitine supplementation for 2 weeks in terminally ill HIV/AIDS patients does not improve fatigue. This study might help to determine the dose and duration of treatment used in future clinical trials, as higher doses and/or longer periods of supplementation might be needed in order to detect an improvement. The reduction in serum lactate levels suggests a potential role for L-carnitine supplementation in patients undergoing certain types of antiretroviral therapy. This study contributes evidence-based data to the field of alternative and complementary medicine, a multibillion dollar industry in which controlled studies are not the norm. Keywords: acquired immune deficiency syndrome, human immunodeficiency virus, fatigue, lactate, L-carnitine supplementation, carnitine deficiency, palliative care